UTILIZING SMARTPHONE SENSORS FOR SIMPLE HARMONIC MOTION ON A DOUBLE SURFBOARD - Lestari, Ristya Dewi; Raharja, Endra Putra; Kumalasari, Lina (PILLAR OF PHYSICS EDUCATION, 2024)
The aim of this research is to develop a simple harmonic motion experiment guide based on smartphone sensors for use on a double surfboard sports vehicle that is valid, practical, and effective. This study applies the Research and Development (R&D) method using the ADDIE development model, which includes five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results show that the accelerometer sensor on a smartphone can effectively measure the period value in the double surfboard sports experiment. The experimental guidebook developed in this study demonstrates high validity, with an average score of 3.53 (88.33%) from media experts and 3.43 (85.75%) from material experts. Practicality testing, based on student responses, resulted in an average score of 3.48 (87.16%), indicating that the guide is highly suitable for use in the learning process. Furthermore, effectiveness testing through pretest and posttest assessments of 17 students showed an improvement in student understanding, with an n-gain value of 0.45, categorized as "medium." Consequently, this guidebook serves as an effective learning tool for enhancing students' comprehension of simple harmonic motion concepts.